ANALISIS EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI KECAMATAN BALIGE KABUPATEN TOBA SAMOSIR - Marwin, Natha; Zakaria, Wan Abbas; Situmorang, Suriaty (Lampung University, 2021)
The study aims to identify the factors that affect lowland rice production, analyze the efficiency of using the production factors of the farming, and calculate the farmersâ€™ income of the farming in Balige Sub-district Toba Samosir Regency. The research was conducted in Hutagaol Peatalun Village and Hinalang Bagasan Village with 64 respondents. Farmer respondents were chosen using a simple random sampling method. The collected data were analyzed by Cobb-Douglas production function, economic analysis by calculating the returm to scale value, and farmer income analysis. The results showed that the factors that affected the production of lowland rice was land size, seeds, NPK fertilizer, pesticide, and labour. The use of production factors were not efficient because it was classified to increasing return to scale. The income earned by the farmers over the total cost was IDR24,636,334.99 with R/C value of 3.89 and it was profitable. Â Key words: efficiency, income, production, lowland rice.